CLINICAL PROFILE OF PATIENTS WITH ACUTE APPENDICITIS ADMITTED AT A TERTIARY CARE HOSPITAL - Dr Bhushan M; Dr B.M. Praveen Kumar; Dr Harini V.; Dr Ashuthosh A. (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
With the modernization and industrialization, more and more people have been adopting a way of life mimicking the western population. The change in the way of life, the effect of the western culture on the eastern population has led to a lot of changes in their diet and is the leading cause behind predisposition to appendicitis. The incidence of the disease is said to be higher with the increase in the socio economic status, among all the diseases; the one of the rare diseases which increases with economic growth. Migration from the rural areas to the urban areas has been implicated in the etiology of appendicitis. Patient diagnosed with acute appendicitis which includes clinical and radiological were chosen. The patients were briefed regarding the study methodology and the purpose of the study. Those willing underwent a detailed evaluation after taking a written consent. 41.30% were males and 58.70% were females . We noted that all cases had a clinical diagnosis of the acute appendicitis.